INFLUENCE OF UNEMPLOYMENT ON THEFTS (CRIMINOLOGICAL RESEARCH) - S. G. Ol’kov (Russian Journal of Economics and Law, 2014)
RETRACTION:Date of retraction: 13.03.2017Reason for retraction: Duplicate publication in several editions Additional information about the causes of retraction:The article “Influence of unemployment on thefts  (criminological research)”, written by S. G. Ol'kov, is a duplicate publication. Information from public databases allowed the editors of the journal "Actual Problems of Economics and Law" to identify a violation of publication ethics. Article by S.G. Ol'kov "Influence of unemployment on thefts  (criminological research)", published in the scientific journal "Actual problems of economics and law". 2014. No. 1. S. 273-276, retracted with the consent of the author, editor-in-chief and publisher.